Assessing bronchodilator response in preschool children using spirometry. Issue 4 (14th October 2016) - Busi, Luciano E; Restuccia, Sebastián; Tourres, Ricardo; Sly, Peter D
Abstract : Background: Measuring lung function, including bronchodilator response (BDR), is an integral part of asthma management in older children. While spirometry is possible in preschool-aged children, the question remains whether measuring BDR aids in asthma diagnosis in this age group. Methods: 431 healthy children and 289 children with asthma, aged 3–5 years, were recruited from kindergartens and the pulmonology clinic in Trelew, Argentina. Spirometry was performed at visit 1 and repeated after 15 min, with children randomised to placebo or salbutamol (400 µg). Spirometry was again performed within 8 weeks at visit 2. Within-session repeatability from visit 1 and between-session reproducibility were calculated using baseline spirometry. The within-session repeatability and receiver operating characteristic curve analyses were used to determine the optimal threshold values for BDR for spirometry outcome variables measured at the first visit, and sensitivity, specificity and diagnostic accuracy were determined. Results: As a group, children with asthma had lower lung function (FVC 1.11±0.12 L vs 1.01±0.15 L; FEV0.75 1.01±0.10 L vs 0.91±0.15 L) and a greater BDR (FEV0.75 group difference 8.6 (95% CI −5.0 to 14.3)%) than healthy children. BDR was best defined by change in FEV0.75 ; an increase of 11% showed the best balance between sensitivity (51%), specificity (88%), positive predictive value (47%) and negative predictive value (89%) for discriminating healthy from preschool-aged children with asthma. Conclusions: A negative BDR in a child suspected of having asthma makes a diagnosis of asthma less likely.